Tool Traces in the Classical Antiquity and Mediaeval quarries of Dalmatia as an Aid in the Chronological Definition of Individual Stages of Exploitation (Archaeologia Adriatica, 2014)
This paper analyses the possibility of the existence of certain differencesin the traces of quarrymen’s tools in Classical Antiquity, mediaeval, and certain early modern era quarries. The aforementioned traces are evident in the form of striae on rocks in the exploited parts of the quarries. Based on analyses of quarries containing a sufficient amount of elements for closer dating, the paper concludes that there are significant differences between Classical Antiquity and mediaeval quarries in terms of the density, direction and depth of the striae, as well as important differences in the layout and expansion of the quarries.
Keywords: stone masonry techniques; quarries; tool traces; Dalmatia